KAPASITAS ANTIOKSIDAN MINUMAN SINOM - Ni Ketut Wiradnyani (LPPM Universitas Dhyana Pura, 2018)
ABSTRACTSinom drink is a kind of beverage made from the turmeric rhizome and young tamarind leaves .because it contains antioxidant compounds. The study aimed to determine the highest antioxidant capacity of the solvent treatment fractions: hexane, chloroform, ethyl acetate and water in vitro. This study used a Randomized Block Design (RBD). The solvent faction significantly influence (p <0.05) on the antioxidant capacity and extraction of Sinom drink in vitro. The LSD multiple comparison test results showed that between the solvent fraction, there is a marked difference in the average of the antioxidant capacity and extraction. The AAEAC antioxidant capacity of 199 100 μg / g of material and 10.94% of extraction was the highest on the fraction of water. The findings of the research indicate that the highest antioxidant capacity water fractions of the Sinom drink’s was 199 100 μg /g AAEAC.Keywords: The Sinom Drinks, the Antioxidant Capacity, fraction of solvent